Comprehensive review on the application of bio-rejuvenator in the regeneration of waste asphalt materials. (9th August 2021) - Fang, Ying; Zhang, Zhengqi; Yang, Jianhua; Li, Xinjun
Highlights: Bio-rejuvenators include wood fiber, animal manure and waste oil types. Bio-rejuvenator improves cracking resistance and moisture resistance. Bio-rejuvenator reduces high temperature performance of aged asphalt. Bio-rejuvenator restores the composition and performance of aged asphalt. Abstract: To make full use of massive waste asphalt materials produced in the road construction and maintenance, and to solve the problems of low efficiency and poor environmental protection of petroleum-based rejuvenators, bio-rejuvenator was proposed to regenerate the waste asphalt materials. The bio-rejuvenator is a green, environmental protection and renewable material, which has a very wide application prospect in the regeneration. For the purpose of promoting the later research and application of bio-rejuvenator, this review summarizes the research progress of bio- rejuvenator in the regeneration of waste asphalt materials. The review results show that the bio-rejuvenator can significantly improve the low-temperature performance of waste asphalt binder, and restore its high-temperature performance to the level consistent with the virgin asphalt. Moreover, the bio-rejuvenator of waste oil type is studied most at present, and its optimum dosage is kept within about 18%, followed by wood fiber type, with a recommended optimum dosage of 5% 20%. There are relatively few studies regarding animal manure type-rejuvenator, and the optimal dosage of swine manure-based bio-rejuvenator is approximately 5% 10%. The addition of bio-rejuvenators can restore the chemical composition and pavement performance of aged asphalt, and achieve its regeneration. Among them, these four bio-rejuvenators of waste soybean oil (WSO), tung oil (TO), waste vegetable oil (WVO) and waste cooking oil (WCO) can significantly decrease the functional group index of aged asphalt, and WCO and 9% waste pig fat (WPF) can restore the four component content distribution of aged asphalt to the same level as virgin asphalt. Furthermore, the bio-rejuvenated asphalt mixture possesses good low-temperature crack resistance, moisture resistance and fatigue crack resistance; moreover, an appropriate amount of bio-rejuvenator can restore the high-temperature stability of the old asphalt mixture to the same level as that of fresh asphalt mixture. Future researches should be executed from the following aspects: further explore how to raise the utilization rate of waste asphalt material meanwhile guaranteeing the sufficient performance of bio-rejuvenated mixture; further explore the regeneration mechanism of bio-rejuvenator on aged asphalt from the micro- even nano-scale as well as the regeneration effect of bio-rejuvenators from other biomass sources; investigate its application in warm-mixed rejuvenated asphalt mixture while focusing on the regeneration of hot-mixed asphalt mixture by bio-rejuvenator; further research regarding fatigue property of rejuvenated asphalt mixture should be conducted and fatigue life prediction model should be also investigated; forming a unifying technical specification for bio-regeneration technology to standardize its application in the regeneration of waste asphalt materials.